Continuous professional development and instructors' beliefs about and practice of active learning method in Bahir Dar university - Mulugeta Teka Kahsay (College of education, Bahir Dar University, 2023)
The objective of this study was to investigate whether there is an overall difference in instructors' beliefs about and practice of active learning methods as a function of the ongoing continuous professional development, known as Higher Diploma Program (HDP). To achieve this objective, it was essential to examine the level of instructors' beliefs and practice in active learning methods. The participants of the study were 58 university instructors (31 HDP participants and 27 non-participants), selected using a stratified sampling technique from four faculties of Bahir Dar University. They responded to a questionnaire having two parts: beliefs about active learning methods and application of active learning methods. The study first employed one sample t-tests which showed that, though these instructors held significantly stronger beliefs about active learning methods than the expected level, they reportedly implemented active learning methods slightly less frequently than the expected level. Then, after computing means and standard deviations for each of the two groups of respondents (31 HDP participants and 27 non-participants), multivariate analysis of variance (MANOVA) was applied to compare the difference between HDP participants and non-participants in their beliefs and practice of active learning methods (when both dependent variables considered together). The results indicated that there was no significant multivariate difference between HDP participants and non-participants in their beliefs and practices of ALM. However, the univariate analyses proved that the HDP participation had a slightly better impact on the instructors' beliefs about ALM than on their practices of ALM. More precisely, the analysis revealed that instructors who participated in the HDP are not anymore strategic in handling learning situations through deploying appropriate ALM techniques than those who did not take the training.